Orientation-induced properties of anisotropic polyacrylamide thin layer via plasma treatment in liquid crystal system. (15th January 2022) - Lee, Dong Wook; Liu, Yang; Kim, Dong Hyun; Oh, Jin Young; Jeong, Hae-Chang; Seo, Dae-Shik
Graphical abstract: Highlights: ∙ Polyacrylamide layer was exposed to plasma ion beam to be used as a LC alignment layer. ∙ Physicochemical property of plasma treated PAM surface was investigated by AFM and XPS analysis. ∙ Plasma IB induced significant chemical modification on the surface for uniform LC alignment. ∙ IB irradiated PAM film showed the uniform LC alignment and good performances for LC system. ∙ Plasma IB treatment can be a suitable process for applying polymer films to LC system. Abstract: Uniform liquid crystal (LC) alignment was achieved on a polyacrylamide (PAM) film treated by a plasma ion beam (IB), and the alignment status of the LCs was confirmed by polarized optical microscopy and pretilt angle analysis using antiparallel LC cells assembled using the IB-treated PAM (IB-PAM) layer. Physically modified characteristics on the PAM surface caused by the IB treatment were observed by atomic force microscopy. Etching with the IB caused roughness reduction and smoothing on the surface with increased irradiation time. Chemical modifications on the surface were investigated by X-ray photoelectron spectroscopy, whose results demonstrated stoichiometric changes causing formation of CO bonding and polarity on the surface. The IB incident at 40° drives the surface polarity anisotropy and van der Waals interactions with the LC molecules, thereby achieving uniform LC alignment. Thermal endurance tests of the IB-PAM layer showed maintenance of the uniform LC alignment status up to 120 °C. Twisted-nematic cells based on the IB-PAM layer showed suitable electro-optical performance with low operating characteristics. The IB-PAM films also showed high and stable optical transparencies. Thus, IB treatment on polymer layer is deemed suitable for the LC alignment process, and IB-PAM film is an excellent choice for next-generation LC systems.